Testes de germinação e vigor em sementes de feijão irrigado - cultivar BRS FC402 - MARCONDES, Bruno Ruan Rossatti,; LOPES, Adriano da Silva,; MOREIRA, Júlia Neves,; FRANCO, Jhonatan da Silva,; MEDEIROS, Rodinei Domingos,; KRAESKI, Marcos Jefferson, (ANAIS DO ENIC, 2025)
-